Comparing Provider and Client Preferences for HIV Prevention Services in South Africa among Men Who Have Sex with Men. (November 2017) - Shaver, John; Sullivan, Patrick; Siegler, Aaron; de Voux, Alex; Phaswana-Mafuya, Nancy; Bekker, Linda-Gail; Baral, Stefan D.; Wirtz, Andrea L.; Beyrer, Chris; Brown, Ben; Stephenson, Rob
Combination prevention efforts are now recommended toward reducing HIV incidence among men who have sex with men (MSM). Understanding the perceptions of both MSM and service providers is critical to informing the development of prevention packages and ultimately improving intervention effectiveness. This study assessed the preferences of MSM and health service providers in the administration of HIV-prevention efforts. Qualitative data were gathered from a series of separate MSM and health care provider focus groups in 2 South African cities. Participants discussed HIV-prevention services and MSM client experiences within South Africa and identified the 3 most important clinic characteristics and 3 most important HIV-prevention services for MSM clients. Priorities indicated by both MSM and health care providers were confidentiality of visit, friendly staff, and condoms, while discrepancies existed between MSM and providers regarding provider consistency and the provision of pre-exposure prophylaxis/post-exposure prophylaxis (PrEP/PEP) and lubricant as prevention methods. Effective interventions must address these discrepancies through the design of intervention and provider training to optimally accommodate MSM.